Influence of MHD and Porous Media on Peristaltic Transport for Nanofluids in An Asymmetric Channel - Jawad, Qabas K.; Abdulhadi, Ahmed. M. (Iraqi Journal of Science, 2023)
The aim of this  paper is to discuss the influence of nanoparticles and porous media, and magnetic field on the peristaltic flow transport of a couple stress fluid in an asymmetric channel with different wave forms of non-Newtonian fluid. Initially, mathematical modeling of the two dimensions and two directional flows of a couple stress fluid with a nanofluid is first given and then simplified beneath hypothesis of the long wave length and the low Reynolds number approximation. After making these approximations, we will obtain associated nonlinear differential equations. Then, the exact solutions of the temperature distribution, nanoparticle concentration, velocity, stream function, and pressure gradient will be calculated. Finally, the results of drawings for many physical parameters that are of importance for examining the behavior of fluid flow quantities are discussed.